The District Health Information System (DHIS2): A literature review and meta-synthesis of its strengths and operational challenges based on the experiences of 11 countries. Issue 2 (May 2019) - Dehnavieh, Reza; Haghdoost, AliAkbar; Khosravi, Ardeshir; Hoseinabadi, Fahime; Rahimi, Hamed; Poursheikhali, Atousa; Khajehpour, Nahid; Khajeh, Zahra; Mirshekari, Nadia; Hasani, Marziyeh; Radmerikhi, Samera; Haghighi, Hajar; et al.
Background: Health information systems offer many potential benefits for healthcare, including financial benefits and for improving the quality of patient care. The purpose of District Health Information Systems (DHIS) is to document data that are routinely collected in all public health facilities in a country using the system. Objective: The aim of this study was to examine the strengths and operational challenges of DHIS2, with a goal to enable decision makers in different counties to more accurately evaluate the outcomes of introducing DHIS2 into their particular country. Method: A review of the literature combined with the method of meta-synthesis was used to source information and interpret results relating to the strengths and operational challenges of DHIS2. Databases (Embase, PubMed, Scopus and Google Scholar) were searched for documents related to strengths and operational challenges of DHIS2, with no time limit up to 8 April 2017. The review and evaluation of selected studies was conducted in three stages: title, abstract and full text. Each of the selected studies was reviewed carefully and key concepts extracted. These key concepts were divided into two categories of strengths and operational challenges of DHIS2. Then, each category was grouped based on conceptual similarity to achieve the main themes and sub-themes. Content analysis was used to analyse extracted data. Results: Of 766 identified citations, 20 studies from 11 countries were included and analysed in this study. Identified strengths in the DHIS were represented in seven themes (with 21 categories): technical features of software, proper management of data, application flexibility, networking and increasing the satisfaction of stakeholders, development of data management, increasing access to information and economic benefits. Operational challenges were identified and captured in 11 themes (with 18 categories): funds; appropriate communication infrastructure; the need for the existence of appropriate data; political, cultural, social and structural infrastructure; manpower; senior managers; training; using academic potentials; definition and standardising the deployment processes; neglect to application of criteria and clinical guidelines in the use of system; data security; stakeholder communications challenges and the necessity to establish a pilot system. Conclusion: This study highlighted specific strengths in the technical and functional aspects of DHIS2 and also drew attention to particular challenges and concerns. These results provide a sound evidence base for decision makers and policymakers to enable them to make more accurate decisions about whether or not to use the DHIS2 in the health system of their country.